Pengaruh Bahan Ajar Muatan Lokal Panorama Alam di Bengkulu Terhadap Hasil Belajar Kognitif Siswa Kelas V SD Negeri 07 Kota Bengkulu - Sri Astuti; Dalifa Dalifa; Victoria Karjiyati (JURIDIKDAS, 2018)
This study aims to determine the influence of local content of naturalpanoramic materials in Bengkulu on the results of the students of class VSD Negeri 07 Kota Bengkulu. This research is a quantitative research.Theresearch design used was Quasy Experimental Design with design typeThe matching Only Pretest-Posttest Control Group Design, where the testtaking twice before and after giving treatment in the sample class. Thesample in this research is the students of class V SD Negeri 07 KotaBengkulu. The research instrument used is a multiple choice test that isgiven through pretest (before learning) and posttest (after learning takesplace). Data of this research are analyzed by using descriptive andinferential analysis that is t-test. From t-test result with tcount 2,164 andttable 2,005. So, tcount (2.164)> ttable (2.005). The value of tcountobtained is higher than ttable value, it can be concluded that there is thethe influence of local content of natural panoramic materials in Bengkuluon the results of the students of class V SD Negeri 07 Kota Bengkulu.Keywords: Teaching Material, Local Content, Natural Panoramic inBengkulu, Achievement.